CONGENITAL EPULIDIS: A LITERATURE REVIEW - FROM DIAGNOSIS TO TREATMENT - Caroline Ribeiro Lacerda, Anne; Alves Freitas Cruz , Kádja; Helena de Brito Santos Lima, Edithe; Luzia Coelho Bezerra de Carvalho, Isabela; Santos Souza, Isabella; Rodrigues Silva, Nicole; Jordania Lino Figueredo, Lívia; Meira Soares, Mariana; de Souza Pereira, Malvina; Jessica Dos Santos Nascimento , Ana (Health and Society, 2025)
Introduction: Congenital epulis is a rare condition characterized by the growth of benign tumors in the oral cavity of newborns or young children. Although it is an uncommon disorder, it is important due to its impact on oral health and child development. Objective: This literature review aims to address the specificities of the diagnosis and treatment of Congenital Epulis. Methodology: The databases used were: National Center for Biotechnology Information, U.S. National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO) and Virtual Health Library (BVS), in English, Spanish and Portuguese. Fifty-three articles published between 2014 and 2024 were selected, and those that did not meet the inclusion criteria were excluded; only xx scientific articles were included in this work. Results: The studies show that ECGC is a rare condition, predominantly identified in female patients, reinforcing hypotheses related to hormonal factors. Surgical treatment has demonstrated high efficacy, with favorable prognosis and low incidence of recurrence. Discussion: Diagnosis is usually made through clinical examination, associated with imaging tests and biopsy, when necessary, to confirm the benign nature of the lesion. Even so, early diagnosis is limited in contexts with restricted access to resources, therefore, diagnosis tends to occur only after birth, through clinical and visual evaluation of the lesion. Conclusion: Congenital epulis requires an accurate diagnosis to ensure the exclusion of other more serious oral conditions. With uncertain etiology of the lesion, surgical treatment, in many cases, is curative and effective, and the prognosis for the child is generally positive.